The Implementation of Simple Additive Weighting Method for Designing A Web-Based Waste Management Saving Transaction System - Nursalim; Muhamad Ziaul Haq; Nalis Hendrawan; Roy Mubarak; I Putu Dody Suarnatha (Jurnal Sistim Informasi dan Teknologi, 2023)
The Garbage Bank is an organization initiated for all students to support the management of inorganic waste into something of value so as to create additional income. The increasing number of customers has caused the treasurer to be overwhelmed in ranking customer rankings and to not be on target in determining the best customer with the same amount of waste. In addition, there is no system security in handling the transaction process, so unwanted access can occur. The purpose of this research is to develop a savings transaction system for waste management so that it becomes a green Campus. The decision-making method uses Simple Additive Weighting. The system development methodology used is Rapid Application Development (RAD). The tools used in system design are the Unified Modeling Language. The implementation of this system uses the PHP programming language with the Laravel and MySQL frameworks for database processing. The resulting system can simplify and speed up the process of recording and managing waste bank data.